2013
DOI: 10.1136/jramc-2013-000087
|View full text |Cite
|
Sign up to set email alerts
|

A brief history of British military experiences with infectious and tropical diseases

Abstract: Infectious and tropical diseases have been a problem for British expeditionary forces ever since the Crusades. Outbreaks were especially common on Navy ships from the 16th to 18th centuries due to poor living conditions and travel to the tropics. However, since these occurred in small, isolated and controlled environments it meant that naval medical practitioners were able to keep detailed records and develop empirical approaches for their prevention. The first Royal Naval Hospitals were established in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This has always been the case in the history of warfare, and Afghanistan was no exception,29 with the challenges facing military physicians on this deployment being well documented 30. Military medicine has firmly placed itself on the front stage again with 22 Field Hospital, 5 Medical Regiment and RFA Argus deploying to Sierra Leone in October 2014 on Op GRITROCK, within days of Bastion Hospital closing, as part of the UK's response to the Ebola crisis in West Africa.…”
Section: Combat Casualty Carementioning
confidence: 99%
“…This has always been the case in the history of warfare, and Afghanistan was no exception,29 with the challenges facing military physicians on this deployment being well documented 30. Military medicine has firmly placed itself on the front stage again with 22 Field Hospital, 5 Medical Regiment and RFA Argus deploying to Sierra Leone in October 2014 on Op GRITROCK, within days of Bastion Hospital closing, as part of the UK's response to the Ebola crisis in West Africa.…”
Section: Combat Casualty Carementioning
confidence: 99%
“…The first British experts in infection were Royal Navy physicians such as Dr James Lind (1716–1794) followed by Royal Army Medical Corps (RAMC) physicians and microbiologists as more cases were seen from overseas campaigns and colonies 2. The most influential figure in the history of sexual health in the Army was Colonel LW Harrison (Figure 1) who transformed the service that managed troops with ‘venereal disease’ (VD).…”
Section: The Pastmentioning
confidence: 99%
“…1 British armies have grappled with these diseases since the Crusades, and even more so during the time of empire. 2 Within living memory, infection was the greatest threat to even the most powerful of military forces. In his account of the Burma Campaign, Defeat into Victory , Field Marshall William Slim said, 'In 1943 for every man evacuated with wounds we had 120 sick…A simple calculation showed that in a matter of months, at this rate my army would have melted away.'…”
Section: Introductionmentioning
confidence: 99%